2000
DOI: 10.1046/j.1365-2540.2000.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary dynamics of male-killers and their hosts

Abstract: Male-killing bacteria are cytoplasmic sex-ratio distorters that are transmitted vertically through females of their insect hosts. The killing of male hosts by their bacteria is thought to be an adaptive bacterial trait because it augments the fitness of female hosts carrying clonal relatives of those bacteria. Here we attempt to explain observations of multiple male-killers in natural host populations. First we show that such male-killer polymorphism cannot be explained by a classical model of male-killing. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 17 publications
4
75
1
Order By: Relevance
“…The first hypothesis is that the fitness of male killers is frequency dependent. Theory predicts that frequency dependence can result if there are costly host genes that confer resistance to specific male killers (Randerson et al 2000). Models of host genes that confer resistance against specific parasite (Barrett 1988) or sex-ratio-distorter (Frank 1989) genotypes also predict the geographical variation that we observed.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The first hypothesis is that the fitness of male killers is frequency dependent. Theory predicts that frequency dependence can result if there are costly host genes that confer resistance to specific male killers (Randerson et al 2000). Models of host genes that confer resistance against specific parasite (Barrett 1988) or sex-ratio-distorter (Frank 1989) genotypes also predict the geographical variation that we observed.…”
Section: Discussionmentioning
confidence: 60%
“…One important factor that may influence the dynamics of sexratio distorters is antagonistic coevolution with nuclear genes. For example, theoretical models have shown that if there are specific gene-for-gene-type interactions between sex-ratio distorters and their hosts, then both the cytoplasmic and nuclear genes may be highly polymorphic (Frank 1989;Randerson et al 2000). Furthermore, instead of reaching a stable equilibrium the two sets of genes may cycle in frequency through time (Charlesworth 1981;Gouyon et al 1991).…”
mentioning
confidence: 99%
“…In two‐distorter simulations with low suppressor costs, the first distorting cytotype was lost after the spread of its suppressor, immediately followed by the invasion of the second distorting cytotype, mirroring the pattern predicted by Randerson et al. (2000). Subsequent alternating cycles of the two distorting cytotypes prevented the spread of the wild cytotype, allowing a consistent female bias to be maintained over time (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
“…Symbioses between Wolbachia and their hosts may be further complicated by evidence for considerable involvement of host nuclear genes in the expression of Wolbachia phenotypes (eg, Poinsot et al, 1998;Bordenstein and Werren, 2000;McGraw et al, 2001;Olsen et al, 2001;this report). Although the competing interests of Wolbachia and such host resistance genes have been modeled previously (eg, Randerson et al, 2000), more empirical work is needed to determine which host genes might be involved.…”
Section: Discussionmentioning
confidence: 99%